Time to Flexible Sigmoidoscopy or Colonoscopy in Patients Admitted With Ulcerative Colitis Has Decreased From 2012 to 2018. Issue 4 (5th December 2021) - Bali, Aman S; Picco, Michael F; Hashash, Jana G; Farraye, Francis A; Kröner, Paul T
Abstract: Background: Early endoscopic evaluation of patients with ulcerative colitis (UC) enables assessment of disease activity and accurate diagnosis based on exclusion of other similarly presenting conditions including infections. Early endoscopy is also associated with improved outcomes of patients with active UC. The aim of this study was determining temporal trends in endoscopy in patients with UC over a 7-year period from 2012 to 2018. Methods: Retrospective cohort study using the National Inpatient Sample 2012–2018. Patients admitted with ICD-9–10 principal codes for UC were included. Early endoscopy using flexible sigmoidoscopy (FS) or colonoscopy was defined as performed within 48 hours of admission. The primary outcome was trends in endoscopy timing. Secondary outcomes were inpatient morbidity, mortality, length of stay (LOS), and hospitalization charges/costs comparing patients undergoing early vs nonearly endoscopy using multivariable regression. Results: Of 222 460 patients hospitalized with UC, 5900 (2.7%) underwent FS and 43 345 (19.5%) underwent colonoscopy. The rate of endoscopy increased from 3.9% (2.3% early) to 39.3% (23.3% early) from 2012 to 2018 ( P < .01). Early endoscopy was associated with statistically significant decreased mortality, shock, multiorgan failure, and intensive care unit odds, as well as decreased resource utilization and LOS. Conclusions: In patients hospitalized with UC, early endoscopy rates were low but performed more frequently from 2012 to 2018. This may reflect increasing awareness of improved outcomes from earlier disease staging and/or diagnosis. Early endoscopy was associated with decreased resource utilization and hospitalization-related outcomes, highlighting the importance of early endoscopy in patients admitted with UC. Lay Summary: We used the National Inpatient Sample to investigate temporal trends in endoscopy in patients hospitalized with ulcerative colitis. Endoscopy within 48 hours of admission happened more often from 2012 to 2018 and was associated with improved patient- and hospitalization-related outcomes.